2021
DOI: 10.3390/f12070871
|View full text |Cite
|
Sign up to set email alerts
|

How Dead Wood in the Forest Decreases Relaxation? The Effects of Viewing of Dead Wood in the Forest Environment on Psychological Responses of Young Adults

Abstract: The intensity of the neutral environment impact on humans may be determined by specific features of space, including dead wood occurrence. Dead wood is claimed to be disliked by the public because it reduces the scenic beauty and recreational values of the forest. The attractiveness of a forest with dead wood may be determined by its variants. Much is known about the preference for landscape with dead wood, but there is little information available about how such a landscape affects a person’s mental relaxatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
(114 reference statements)
1
7
0
Order By: Relevance
“…4.1.2 Autumn bare tree landscapes also contribute to recovery. Previous research has shown that bare tree landscapes significantly influence psychological relaxation and emotional improvement in individuals [45], aligning with our study's results. Even in seasons where plant colors are relatively monochromatic, bare tree landscapes still exhibit notable effects on mental recovery.…”
Section: Impact Of Seasonal Landscape Color Types On Recovery Effectssupporting
confidence: 92%
“…4.1.2 Autumn bare tree landscapes also contribute to recovery. Previous research has shown that bare tree landscapes significantly influence psychological relaxation and emotional improvement in individuals [45], aligning with our study's results. Even in seasons where plant colors are relatively monochromatic, bare tree landscapes still exhibit notable effects on mental recovery.…”
Section: Impact Of Seasonal Landscape Color Types On Recovery Effectssupporting
confidence: 92%
“…Further research by Janeczko et al, showed that environmental diversity helps to improve mood and has greater recovery. At the same time, natural protection forests will have a better relaxation effect on people in terms of emotional state, subjective vitality and restoration than artificially managed forests [20].…”
Section: The Beauty and Rehabilitation Effect Of The Landscape In Urb...mentioning
confidence: 99%
“…Son and Ha [38] found that increasing contact with nature improves social and emotional interactions in modern society. Our previous research [39,40] also indicates that the forest environment has a relaxing effect associated with an increase in positive emotions.…”
Section: Discussionmentioning
confidence: 82%